Application of dissociation curve analysis to radiation hybrid panel marker scoring: generation of a map of river buffalo (B-bubalis) chromosome 20 - Kochan, Kelli J.; Amaral, M. Elisabete J. [UNESP]; Agarwala, Richa; Schaeffer, Alejandro A.; Riggs, Penny K. (Biomed Central Ltd., 2008)
Background: Fluorescence of dyes bound to double-stranded PCR products has been utilized extensively in various real-time quantitative PCR applications, including post-amplification dissociation curve analysis, or differentiation of amplicon length or sequence composition. Despite the current era of whole-genome sequencing, mapping tools such as radiation hybrid DNA panels remain useful aids for sequence assembly, focused resequencing efforts, and for building physical maps of species that have not yet been sequenced. For placement of specific, individual genes or markers on a map, low-throughput methods remain commonplace. Typically, PCR amplification of DNA from each panel cell line is followed by gel electrophoresis and scoring of each clone for the presence or absence of PCR product. To improve sensitivity and efficiency of radiation hybrid panel analysis in comparison to gel-based methods, we adapted fluorescence-based real-time PCR and dissociation curve analysis for use as a novel scoring method.Results: As proof of principle for this dissociation curve method, we generated new maps of river buffalo (Bubalus bubalis) chromosome 20 by both dissociation curve analysis and conventional marker scoring. We also obtained sequence data to augment dissociation curve results. Few genes have been previously mapped to buffalo chromosome 20, and sequence detail is limited, so 65 markers were screened from the orthologous chromosome of domestic cattle. Thirty bovine markers (46%) were suitable as cross-species markers for dissociation curve analysis in the buffalo radiation hybrid panel under a standard protocol, compared to 25 markers suitable for conventional typing. Computational analysis placed 27 markers on a chromosome map generated by the new method, while the gel-based approach produced only 20 mapped markers. Among 19 markers common to both maps, the marker order on the map was maintained perfectly.Conclusion: Dissociation curve analysis is reliable and efficient for radiation hybrid panel scoring, and is more sensitive and robust than conventional gel-based typing methods. Several markers could be scored only by the new method, and ambiguous scores were reduced. PCR-based dissociation curve analysis decreases both time and resources needed for construction of radiation hybrid panel marker maps and represents a significant improvement over gel-based methods in any species.